Hormone dependency in metastatic low-grade leiomyosarcoma following uterine smooth muscle tumour of uncertain malignant potential. (27th March 2014) - Serrano, Cesar; Nucci, Marisa R; Tirumani, Sree H; Raut, Chandrajit P; George, Suzanne
Abstract : Uterine leiomyosarcoma (ULMS) usually follows an aggressive clinical course, although a small proportion of ULMS exhibit a more indolent course, which in turn reflects heterogeneity within this disease and the need to identify and characterise this distinct subgroup. The role of hormone therapy in ULMS is yet to be elucidated. We report a patient with well-differentiated metastatic ULMS on hormone replacement therapy (HRT) at the time of the diagnosis. The withdrawal of the HRT led to a significant decrease in the tumour burden and symptomatic improvement. The patient further benefited from aromatase inhibitor treatment once the benefit from the HRT withdrawal reached a plateau. The present case report describes for the first time hormone-dependency for tumour growth in a ULMS. We propose that a subset of ULMS that follow a protracted/indolent course might depend on hormone stimulation for tumour proliferation, and antihormone treatment can therefore be useful in these patients.